Modelling Monthly International Tourist Arrivals and Its Risk in Nepal - Neupane, Hari Sharma; Shrestha, Chandra Lal; Upadhyaya, Tara Prasad (NRB Economic Review, 2012)
The volume of international tourist arrivals is the prime concern for both the tourism entrepreneurs and policy makers, as the arrivals is directly associated with foreign exchange earnings or export benefits, and tourism induced economic activities. The overall average annual growth of international tourist arrivals in the country over the last 40 years is about 6.65 percent. The mean contribution of tourism sector as a percentage of GDP was 2.67 percent during the last 35 years. This paper explores the risk associated in the Nepalese tourism industry taking account of monthly international tourist arrivals. The symmetric and asymmetric conditional mean and volatility models, GARCH, GARCH-GJR and EGARCH with exogenous ARMA terms were applied for data analysis. The empirical results showed that the long run risk or volatility is persistence in monthly international tourist arrivals and estimated coefficients are statistically significant. The volatility can be inferred as risk or uncertainty associated with international tourist arrivals in Nepalese tourism industry. Therefore, this empirical study envisages sufficient room for intervening or amending the tourism policy to better attract international visitors and promote tourism as a business.